PROSES PENDINGINAN AIR DENGAN LIMBAH BATU BATA - Muh Syukri Ahsani; Husna Noor Mufida; Masturi Masturi; Ian Yulianti (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
PDAM water reservoir or water in the tub was hot during the day and less convenient to use for bathing. The water needs to be cooled down 2-50C to make it more convenient to use. One method that is inexpensive to cool water that pass through a gap broken bricks. The study was conducted by the length variation of water flow through the gap broken bricks. Furthermore, the temperature of the water before and after the gap of broken bricks were measured using a mercury thermometer. The analysis is done by comparing the tables and graphs to analyze the relationship between the length of the flow to the drop in temperature. The results showed that the most effective water cooling process by passing the gap of broken bricks a long stream of 1 meter. Keywords : cooling water , temperature , bricks.